PENGARUH BEBAN KERJA, GAYA KEPEMIMPINAN, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN PAPUA BARAT DAYA - Derek Gifelem,; Bambang Raditya Purnomo,; Rinadini Hendrasworo, (Journal of Innovation Research and Knowledge, 2025)
Objectives: The study analyzes the influence of Workload, Leadership Style and Work Motivation on the Performance of Employees at the Southwest Papua Province Transportation Office partially and simultaneously. Methodology: This research is quantitative and the sample consisted of 46 employees of the Southwest Papua Transportation Agency. The research methodology used a survey approach with questionnaire distribution. The data analysis technique used was multiple linear regression to test the influence of each variable, both partially and simultaneously, on employee performance. Finding: The results of the study indicate that partially, workload has a significant negative effect on employee performance, leadership style has a significant positive effect on employee performance, and work motivation has a significant positive effect on employee performance. Simultaneously, workload, leadership style, and work motivation have a significant effect on employee performance. Conclusion: The findings of this study provide implications for human resource management, particularly in the arrangement of proportional workloads, the application of effective leadership styles, and increasing work motivation to encourage optimal employee performance